INVIVO STUDY OF AQUEOUS EXTRACT OF SNAKE FRUIT SEEDS IN FEMALE RATS WITH ANEMIA - Fara Ayu Febyawati, Hani; Indarto, Dono; Handayani, Selfi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Anemia remains a global nutritional problem in children, pregnant women and female adolescents because of increasing its prevalence. This study aimed to analyze the effects of aqueoes extract of snake fruit seed (AES) on body weight (BW), body length (BL), body fat percentage (BFP), and wet organ weight in female rats with anemia. This animal experiment used the pre-posttest control group design. A total of 30 female wistar rats with anemia were randomly divided into 5 groups: the negative and positive control groups were given a low iron diet with or without administration of 3.7 mg/200gBW iron supplements, and the treatment (AES1-3) groups were given a low iron diet+AES administration (25,50, and 100 mg/200gBW respectively) for 28 days. Data were analyzed using SPSS 26.0, and STATA MP 17. The average of BW, wet liver and kidney weights in the AES2 group significantly increased, compared to other rat groups. The average of BFP in the AES2 group significantly decreased, compared to the control groups. The average of BL and wet spleen weight did not differ among rat groups. In conclusion, administration of 50 mg/200gBW AES increases BW, wet organ weights, and decreases BFP, but has no effect on BL.